Balancing Mechanical Stability and Ultrahigh Porosity in Crystalline Framework Materials. Issue 42 (24th September 2018) - Hönicke, Ines M.; Senkovska, Irena; Bon, Volodymyr; Baburin, Igor A.; Bönisch, Nadine; Raschke, Silvia; Evans, Jack D.; Kaskel, Stefan
Abstract: A new mesoporous metal–organic framework (MOF; DUT‐60) was conceptually designed in silico using Zn4 O 6+ nodes, ditopic and tritopic linkers to explore the stability limits of framework architectures with ultrahigh porosity. The robustith‐d topology of DUT‐60 provides an average bulk and shear modulus (4.97 GPa and 0.50 GPa, respectively) for this ultra‐porous framework, a key prerequisite to suppress pore collapse during desolvation. Subsequently, a cluster precursor approach, resulting in minimal side product formation in the solvothermal synthesis, was used to produce DUT‐60, a new crystalline framework with the highest recorded accessible pore volume (5.02 cm 3 g −1 ) surpassing all known crystalline framework materials. Abstract : Pores for thought : Computational prediction suggests DUT‐60 as a new framework with sufficient mechanical stability to enable exceptional gas accessible porosity. With an experimentally validated specific surface area of 7839 m 2 g −1 and a specific pore volume of 5.02 cm 3 g −1 DUT‐60 has the highest ever achieved porosity among all crystalline porous frameworks.